Pengaruh struktur kepemilikan pada perusahaan keluarga yang terdaftar di Bursa Efek Indonesia: dimoderasi oleh Karakteristik Dewan - Santi Yopie; Caroline Hakim (Politeknik Ganesha Medan, 2022)
This study was to examine family ownership, institutional ownership, managerial ownership, and foreign ownership on the performance of family firms. In addition, this study will also examine family ownership which is moderated by the independent board of commissioners and the board of directors. This study uses quantitative methods and is tested using the SPSS application and E-views. The sample in this study is a family company listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. The company's performance variable in this study is measured by Tobin's Q. This study will conduct three tests. The first test is all variables without moderation. The second test is family ownership which is moderated by an independent board of commissioners. The third test is family ownership which is moderated by the board of directors. The results of this study are family ownership and foreign ownership have a significant positive effect on company performance. Meanwhile, institutional ownership, managerial ownership, family ownership moderated by an independent board of commissioners, and family ownership moderated by a board of directors have an insignificant effect on company performance. The results of this study can conclude that not all share ownership can affect the performance of a company.